La preuve devant les tribunaux administratifs et quasi judiciaires - Garant, Patrice (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1980)
Procedure before quasi-judicial boards and tribunals has recently attracted abundant comment as well as some criticism. In administrative law, rules of evidence form an important part of procedure. In this paper, the author first tries to define what are the sources of the law of evidence before quasi-judicial agencies in Québec : the common law, the two Codes, statutes and regulations. Then follows in two parts an overview of the principal rules that govern the manner in which claims and arguments are brought before tribunals and the extent to which specific provisions or general principles of administrative law allow tribunals themselves to gather evidence required for the purposes of a decision. The paper suggests that administrative justice requires that the tribunal really be « master of the procedure », within the framework of natural justice.